Fatty Acid Profile And Hydrocarbon Characterization Of Nitzschia Closterium (W.Sm.) - R.SUGAPRIYA,; S.SRISUDHA,; P. GUNASEKARAN, (International Journal of Pharma and Bio Sciences, 2012)
Lipid productivity is a critical variable for evaluating algal species for biodiesel production. The pennate diatom Nitzschia closterium (W. Sm.) isolated from the local water body of Madurai was cultivated in four different media (WCg, Csi, F/2 and Diatom medium) and screened for the presence of neutral lipid content using Nile red fluorescent dye. The relative abundance of lipid content was estimated by fluorescence spectroscopy using Nile red. The numbers of cells exhibiting fluorescence were found to increase on 10th day in comparison to 5th day in the strain Nitzschia closterium. The maximum lipid production was noticed in Nitzschia closterium grown at pH -7. Green and orange color bands developed in the thin layer chromatography indicated the presence of chlorophyll a and fucoxanthin pigments. Thin Layer Chromatography of the extracted lipid fractions revealed the presence of Monoacylglycerols, Diacylglycerols and Triacylglycerols. Gas Chromatography confirmed the presence of fatty acids such as Myristic (14:0), Palmitic (16:0), Stearic (18:0) and other FAMES in the isolated strain. In addition, high molecular weight hydrocarbons were detected using GC-MS analysis. The higher percentage of lipid and fatty acids indicate the suitability of this indigenous organism as a potential source for algal bio-fuel.